Surface modification effect of Li3NbO4 on LiNi0.5Co0.2Mn0.3O2 cathode material under varying voltage and temperature conditions - Park, Jae-Ho; Kim, Min-Young; Jeong, Jiwon; Kim, Mingony; Jung, Hun-Gi; Yoon, Woo Young; Chung, Kyung Yoon (Elsevier BV, 2025)
Lithium-ion batteries (LIBs) play a key role in energy storage applications due to their high energy density and long cycle life. However, the structural and electrochemical degradation of cathode materials, especially under high-voltage and high-temperature conditions, remains a critical challenge. In this study, we address these issues by applying surface modification to LiNi0.5Co0.2Mn0.3O2 (NCM523) using Li3NbO4 (LNbO) through a solid-state coating method. This surface modification aims to suppress adverse side reactions, enhance structural stability, and improve both electrochemical performance and thermal stability. Our findings show LNbO coating effectively mitigates undesirable phase transitions, such as the formation of spinel and rock-salt structures, and significantly improves cycling stability. Furthermore, this study shows that the optimal LNbO coating ratio varies depending on specific operating conditions, and adjusting the coating thickness according to the voltage and temperature requirements is important. It also demonstrates that the coating improves thermal stability. This study highlights the potential of LNbO surface modification as a scalable and practical strategy to improve the performance and safety of NCM-based cathodes, particularly for high-performance LIBs in EV and ESS applications, where both high energy density and thermal stability are essential.